Justice Collaborator Bagi Tersangka Bharada E Dalam Tindak Pidana Pembunuhan Berencana Brigadir J - Septian, Akhmad Rizky; Mudiparwanto, Wahyu Adi (VIVA THEMIS, 2023)
Justice collaborators are actors who cooperate with law enforcement to uncover serious and organized cases, such as the crime of premeditated murder experienced by Brigadier J. The crime of premeditated murder is an act of murder preceded by a premeditated murder. The purpose of this study was to find out how justice collaborators are regulated in positive law in Indonesia and how to determine justice collaborators for the suspect Bharada E. This research uses normative research methods, with statutory, conceptual and perceptual approaches. The results of the discussion concluded that the regulation or legal basis for justice collaborators in positive law in Indonesia was pioneered from international agreements then ratified, namely Law No. 7 of 2006 regarding the UN Convention Against Corruption. Bharada E submitted an application to LPSK to obtain status as Justice Collaborator on the grounds that Baharada E was not the main perpetrator and was willing to provide information to law enforcement about the actual incident which was later granted by LPSK.